The mechanical behaviour of sandwich structure based on corrugated cores - Rejab, Mohd Ruzaimi Mat; Ishak, M. (2020)
Laser-welded web-core sandwich structures are popularly found in marine transportation. Understanding the effect of geometric parameters on structure stiffness is necessary in order to execute an accurate design. The overhanging three-point bending experiments, along with the simulations of Finite Element (FE) were conducted in this on the laser-welded steel core sandwich plate under quasi-static loading. The parameters of the sandwich structure such as; face plate thickness, the spacing of the two core plate and the core plate height have been analysed under a trace of load-deflection. There was a good agreement between the experimental measurements and the FE performance. Changes to the parameters of web-core sandwich plates that lead to increase or decrease on the stiffness, but the core plates height does not have an effect on the shear stiffness as it is well understood that the distance between the two core plates is small. The geometric and stiffness of web-core sandwich panels experience linear, exponential and polynomial relations under three-point bending test.